PENGEMBANGAN MODEL TANJAK UNTUK MENINGKATKAN KUALITAS DAN PRODUKTIVITAS SMK AL-AQWAM - Hakim, Ikhsan; Suhardi; Nurkulla, Muhammad Mashuri; Bariyah, Oneng Nurul; Sulaiman, Suhendar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop the TANJAK Model (Quality Governance, Quality Culture Actualization, Islamic Values, Industry Partnership Networks, Quality Acceleration, and Productive Performance) as a framework for improving the quality and productivity of private Islamic vocational schools. The study employed a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. Data were collected through observations, interviews, questionnaires, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the TANJAK Model successfully integrates quality governance, quality culture, Islamic values, and industry partnerships into a sustainable school management system. Its implementation improved school quality through data-driven planning, the implementation of Internal Quality Assurance Systems, enhanced learning practices, and increased student participation. School productivity also improved, as reflected in better teacher performance, more effective school programs, stronger industry partnerships, higher graduate competencies, and increased public trust. Therefore, the TANJAK Model is considered a feasible and sustainable quality improvement model for private Islamic vocational schools.